Fragility of asymptotic agreement under Bayesian learning - Muhamet Yildiz; Daron Acemoglu; Victor Chernozhukov (Theoretical Economics, 2016)
Under the assumption that individuals know the conditional distributions of signals given the payoff-relevant parameters, existing results conclude that as individuals observe infinitely many signals, their beliefs about the parameters will eventually merge. We first show that these results are fragile when individuals are uncertain about the signal distributions: given any such model, vanishingly small individual uncertainty about the signal distributions can lead to substantial (non-vanishing) differences in asymptotic beliefs. Under a uniform convergence assumption, we then characterize the conditions under which a small amount of uncertainty leads to significant asymptotic disagreement.
Keywords: C11; C72; D83; 330; Asymptotic disagreement; Bayesian learning; merging of opinions